ISSUES OF VOCAL AND TECHNICAL IMPROVEMENT STUDENTS 'SKILLS FACULTIES OF MUSIC AND PEDAGOGICAL (Pedagogy of Higher and Secondary Education, 2022)
In vocal pedagogies the large role belongs to a professional knowledge, experience and personal qualities of the teacher.